2012
DOI: 10.5296/ijld.v2i1.1325
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Work Environment Facilities

Abstract: A healthful work environment brings safety to employees' physical and mental capabilities in performing their daily routine. In order to reach the healthful work environment, providing the healthful facilities must be taking into account. The examples of facilities are chair seating and lighting. A proper chair seating and sufficient lighting play important role in ensuring employees' welfare are protected as well their work performance goes up. The ignorance of these important healthful work environments will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Working environment and its characteristics were considered as major factors affecting the prevalence of WMSD [24]. This study identified 4 main areas related to working environment and assessed them in relation to the reporting of WMSD in different body regions.…”
Section: Discussionmentioning
confidence: 99%
“…Working environment and its characteristics were considered as major factors affecting the prevalence of WMSD [24]. This study identified 4 main areas related to working environment and assessed them in relation to the reporting of WMSD in different body regions.…”
Section: Discussionmentioning
confidence: 99%
“…The authors encouraged organizations to dedicate sufficient resources to improve personal workspace. Numerous studies support the role that ergonomics plays in employee performance (Asmui et al, 2012). Hanson et al (2007), in an anthropometric research study, noted that there have been significant changes in the physical characteristics of the population and that current ergonomic standards for seating and other office furniture have not been adjusted accordingly.…”
Section: Personal Workpace and Ergonomicsmentioning
confidence: 99%
“…Nigeria's university education has been faced with a high degree of apprehension and recurrent crises of different kinds which have ultimately resulted in the incessant strike embarked by the Academic Staff Union of Universities (ASUU). There are crises of internal governance and vulnerability, favouritism, unsatisfactory work situations such as poor condition of services (Gberevbie, 2008;Ibidunni et al, 2016), severe administrative and organisational structure (Osibanjo et al, 2014); under-funding (Ajayi & Ekundayo, 2010) and inadequate learning and teaching facilities (Abdulsalam & Mawoli, 2012;NUC, 2010); poor relationship with supervisors and colleagues (Asmui et al, 2012); crises of employment relationship (Adeniji & Osibanjo, 2012;Ojeifo, 2014) and continuity (Oredein & Alao, 2010); brain drain, rising absenteeism, and attrition (Gberevbie, 2008;.…”
Section: Introductionmentioning
confidence: 99%